2008
DOI: 10.1161/strokeaha.107.488189
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Matrix Metalloproteinase-9 in Acute Ischemic Stroke

Abstract: Background and Purpose-Experimental stroke studies indicate that oxidative stress is a major contributing factor to ischemic cerebral injury. Oxidative stress is also implicated in activation of matrix metalloproteinases (MMPs) and blood-brain barrier injury after ischemia-reperfusion. Plasma biomarkers of oxidative stress may have utility as early indicators of efficacy in Phase 2 trials of antioxidant therapies in human stroke. To date, a valid biomarker has been unavailable. We measured F2-isoprostanes (F2I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(80 citation statements)
references
References 23 publications
3
74
1
1
Order By: Relevance
“…57 In humans, MMP-9 activity increases early, with a peak at 6 to 8 hours after stroke and a return toward baseline by 24 to 26 hours. 48 MMP-9 mRNA levels are also increased in human peripheral leukocytes at 3 and 5 hours after stroke with a return toward baseline by 24 hours 58,59 ( Figure 4). Thus, there appears to be a transient increase in MMP-9 levels in circulating leukocytes and plasma, with a peak between 2and 8 hours of ischemic stroke onset.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 91%
See 1 more Smart Citation
“…57 In humans, MMP-9 activity increases early, with a peak at 6 to 8 hours after stroke and a return toward baseline by 24 to 26 hours. 48 MMP-9 mRNA levels are also increased in human peripheral leukocytes at 3 and 5 hours after stroke with a return toward baseline by 24 hours 58,59 ( Figure 4). Thus, there appears to be a transient increase in MMP-9 levels in circulating leukocytes and plasma, with a peak between 2and 8 hours of ischemic stroke onset.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 91%
“…47 The rate of early HT and severity of BBB disruption are reduced in mice deficient in NOX2 and when NOX2 is inhibited. 47 In humans, the oxidative stress marker F2-isoprostane is increased in blood early after stroke onset (median 6 hours) 48 and plasma levels of 3-nitrotyrosine are elevated at 3 and 24 hours. 49 Indeed, several clinical factors associated with HT in stroke patients may promote the generation of ROS, including age, glucose, diabetes, infarct size, congestive heart failure, and renal impairment 50 ( Figure 3; Table 1).…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 99%
“…Three studies reported higher levels of plasma F 2 -isoprostanes in ischaemic stroke patients as compared with healthy participants. 31,33,34 In contrast, one study reported that patients with aneurysmal subarachnoid hemorrhage had higher levels of free form of F 2 -isoprostanes after surgery in both plasma and cerebrospinal fluid as compared with controls. 32 Note that only one of the four included studies performed multivariable analysis to control confounding.…”
Section: Strokementioning
confidence: 95%
“…Reactive oxygen species (ROS) have been indicated as one of the earliest and most significant components of tissue injury following reperfusion of the ischemic organ (4,5). The brain is quite vulnerable to oxidative stress due to its high polyunsaturated fatty acid content, which is particularly susceptible to ROS damage (6,7).…”
Section: Introductionmentioning
confidence: 99%